Income convergence during the crisis: did EU funds provide a buffer? - Merler, Silvia (Brussels, 2016)
"This paper shows that economic convergence continued during the crisis for the EU as a whole, although at a slower pace, but for regions in the EU14, and especially in the euro area, convergence appears to have stopped during the crisis, or even switched to a divergence path."